Ketene 3‐Component Staudinger Reaction (K‐3CSR) to β‐Lactams: A New Entry in the Class of Photoinduced Multicomponent Reactions. Issue 22 (10th June 2021) - Minuto, Federica; Lambruschini, Chiara; Basso, Andrea
Abstract: The Staudinger synthesis of β‐lactams from imines and ketenes has been conducted photochemically only in very limited cases. Recent advances in the visible light mediated Wolff rearrangement of diazoketones allowed us to perform, for the first time, a 3‐component Staudinger reaction, by mixing aldehydes, amines and diazoketones in the dark and switching the light on after imine formation. The new photoinduced reaction parallels the classic methods in terms of efficiency/selectivity and adds to the existing multicomponent approaches for the preparation of combinatorial libraries of compounds. A thorough optimization of the reaction conditions was performed both for the classic two component reaction and for the novel three component version of the photoinduced Staudinger reaction. Abstract : The trick is a switch. For the first time, the Staudinger β‐lactam synthesis was performed as a three‐component reaction, by mixing diazoketones, aldehydes and amines all in once. A visible‐light mediated Wolff rearrangement was the key feature for this novel multicomponent reaction. This approach was characterized by complete trans selectivity and yields comparable to those of the classic two component reaction between ketenes and imines.